The influence of individualism and drinking identity on alcohol problems - Foster, Dawn W. (Int J Ment Health Addict, 2014)
This study evaluated the interactive association between individualism and drinking identity predicting alcohol use and problems. Seven hundred and ten undergraduates (Mean age =22.84, SD = 5.31, 83.1% female) completed study materials. We expected that drinking identity and individualism would positively correlate with drinking variables. We further expected that individualism would moderate the association between drinking identity and drinking such that the relationship between drinking identity and alcohol outcomes would be positively associated, particularly among those high in individualism. Our findings supported our hypotheses. These findings better explain the relationship between drinking identity, individualism, and alcohol use. Furthermore, this research encourages the consideration of individual factors and personality characteristics in order to develop culturally tailored materials to maximize intervention efficacy across cultures.